2023
DOI: 10.1186/s12967-023-04149-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteome of Long-COVID patients indicates HIF-mediated vasculo-proliferative disease with impact on brain and heart function

Abstract: Aims Long-COVID occurs after SARS-CoV-2 infection and results in diverse, prolonged symptoms. The present study aimed to unveil potential mechanisms, and to inform prognosis and treatment. Methods Plasma proteome from Long-COVID outpatients was analyzed in comparison to matched acutely ill COVID-19 (mild and severe) inpatients and healthy control subjects. The expression of 3072 protein biomarkers was determined with proximity extension assays and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 77 publications
3
11
0
Order By: Relevance
“…Reports of innate cell perturbations in patients with Long COVID have been published but results are variable and somewhat conflicting 55 . We find monocyte redistribution in favor of CD33-expressing classical monocytes in Long COVID and elevated plasma proteins such as TNFα and TRAIL suggesting ongoing monocyte activation, in line with previous findings 56,57 . Another recent paper reported a dysregulated activation of the complement system, which could be linked to antibody-responses, either to SARS-CoV-2 or to reactivated herpesviruses 58 .…”
Section: Discussionsupporting
confidence: 92%
“…Reports of innate cell perturbations in patients with Long COVID have been published but results are variable and somewhat conflicting 55 . We find monocyte redistribution in favor of CD33-expressing classical monocytes in Long COVID and elevated plasma proteins such as TNFα and TRAIL suggesting ongoing monocyte activation, in line with previous findings 56,57 . Another recent paper reported a dysregulated activation of the complement system, which could be linked to antibody-responses, either to SARS-CoV-2 or to reactivated herpesviruses 58 .…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, recent studies have suggested that patients with LC may suffer from chronic hypoxic changes affecting the brain ( 21 ). Consistent with this, a vascular inflammation associated with hypoxia-inducible factor-1 is reported to contribute to neurological and cardiometabolic dysfunction in LC ( 22 ).…”
Section: Introductionsupporting
confidence: 53%
“…ANGPT1 is increased in the MIS-C cohort and is angiogenic with vascular protective effects [ 99 ]. As a primary regulator of angiogenesis, ANGPT1 is highly elevated in Long-COVID patients [ 27 , 30 , 100 ]. PPBP, also known as CXCL7, is elevated in the MIS-C cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the primary goal of this study was to identify blood proteins specific to MIS-C inpatients relative to age- and sex-matched SCNS patients. Our specific objectives were: (1) to measure a large number of blood proteins from each cohort with targeted proteomics [ 25 30 ]; (2) to determine the relative importance of the proteins with machine learning to differentiate MIS-C subjects; (3) to correlate protein expression with clinically relevant MIS-C variables; and (4) to determine the cell types and organ systems in which the important proteins are expressed.…”
Section: Introductionmentioning
confidence: 99%